2001
DOI: 10.2337/diabetes.50.9.2139
|View full text |Cite
|
Sign up to set email alerts
|

Human Fructosamine-3-Kinase

Abstract: Nonenzymatic glycation appears to be an important factor in the pathogenesis of diabetic complications. Key early intermediates in this process are fructosamines, such as protein-bound fructoselysines. In this report, we describe the purification and characterization of a mammalian fructosamine-3-kinase (FN3K), which phosphorylates fructoselysine (FL) residues on glycated proteins, to FL-3-phosphate (FL3P). This phosphorylation destablilizes the FL adduct and leads to its spontaneous decomposition, thereby rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
129
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(141 citation statements)
references
References 58 publications
11
129
1
Order By: Relevance
“…Estimates reported here are similar to those reported previously [25]. The increased FL urinary excretion in diabetes may underestimate increased formation in diabetes, as FL urinary excretion is metabolised efficiently by fructosamine-3-phosphokinase [26]. FL residues in haemoglobin correlated positively with measures of glycaemic control, HbA 1 c and 24hG, whereas FL residues in plasma protein correlated negatively with CEL and 3DG-H residues.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Estimates reported here are similar to those reported previously [25]. The increased FL urinary excretion in diabetes may underestimate increased formation in diabetes, as FL urinary excretion is metabolised efficiently by fructosamine-3-phosphokinase [26]. FL residues in haemoglobin correlated positively with measures of glycaemic control, HbA 1 c and 24hG, whereas FL residues in plasma protein correlated negatively with CEL and 3DG-H residues.…”
Section: Discussionsupporting
confidence: 87%
“…The concentrations of MG-H1 and 3DG-H in haemoglobin were approximately ten-fold higher than the concentrations of CML and CEL residues, and 100-and 500-fold higher than the concentrations of MOLD and pentosidine residues respectively. Formation of 3DG-H in RBCs may be linked to the formation of 3-DG by the deglycating action of fructosamine-3-phosphokinase on HbA 1 c [26,33]. Application of matrix-assisted laser desorption ionisation (MALDI) mass spectrometry gave evidence of multiple types of modified haemoglobin in diabetes by molecular mass measurement of haemoglobin subunits [34], consistent with the findings of this study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…1,2 If both glycation and deglycation are occurring simultaneously, there is no evidence of a complex time course from mean cell age until cells are removed from the circulation. A deglycating enzyme 43 has recently been identified that acts at lysine, but none has been reported that acts at the N-terminal glycated amino group. 44 The strong correlation of glycation rate with whole blood HbA1c in the DM and NDM subjects ( Figure 5) provides evidence that the whole blood determination depends on the integration of glycation rate throughout the red cell life span.…”
Section: Hba1c Synthesis Ratementioning
confidence: 99%
“…The non-enzymatic reaction of protein amino groups with glucose and other reducing sugars has long been considered irreversible [8,25]. However, recent evidence indicates that fructosamines can be repaired by Fructosamine-3-Kinase (FN3K), which phosphorilates fructoselysine (FL) residues on glycated proteins, resulting in the production of protein-bound FL-3-phosphate (FL3P) [16].…”
Section: Introductionmentioning
confidence: 99%